From Modula to Oberon - Wirth, Niklaus 1934-2024 (1989)
Abstract: "The programming language Oberon is the result of a concentrated effort to increase the power of Modula-2 and simultaneously to reduce its complexity. Several features were eliminated, and a few were added to increase the expressive power and flexibility of the language. This paper describes and motivates the changes. The language is defined in a concise report."
Keywords: Programming languages (Electronic computers)